Impacts of Private Residential Land Development Projects in the Flood Flow Zones of DMDP Area: Case Study of Tetuljhora Union (Journal of Bangladesh Institute of Planners, 2021)
Dhaka the Capital of Bangladesh is experiencing outstanding growth over the last one decade. Dhaka has expanded 17.88 times from its initial size over the period 1951-2000, in the same time span the population has increased 25.09 folds. In response l,) growing demand for housing and other urban uses, private land development companies play a dominating role in the land market. Even though there are sufficient policies for planned development of housing projects, due to high profit making approach of land developer companies, Dhaka is growing in an unplanned way. This is causing adverse effects on the wetlands. For the survival of Dhaka city, it is important to protect the flood flow zones and high value agricultural land. In Tetuljhora union of Savar, housing projects are being developed since the 1980s without following the existing rules and regulations for housing development. Projects are being developed on those areas, where these types of uses are not permitted and they do not follow the standards of PRLD, 2004. So, this area is already facing many environmental, social and economic problems and in the future, if people began to reside here in unauthorized way, they will face problems due to lack of utilities and community facilities. There are problems with planning and development regulatory authorities and loopholes in PRLDR, 2004. To reduce the impacts of unplanned housing projects and ensure planned development of housing projects. measures should be taken to address the loopholes and weaknesses of policy guidelines and regulatory functions.Journal of Bangladesh Institute of Planners Vol. 4. Dec 2011, pp. 57 - 70